Weighing up the evidence: A response to Fischer et al. (October 2016) - Lyons, Kristen; Westoby, Peter
Abstract: This paper responds to the commentary by Fischer et al. (2016) on Lyons, K. and Westoby, P. (2013) Carbon colonialism and the new land grab: Plantation forestry in Uganda and its livelihood impacts, Journal of Rural Studies, 36, 13-21.